Met 'n lied in die hart - Vos, Casparus Johannes Adam (Verbum et ecclesia, 2001)
Psalms are songs that have principal importance in Jewish and Christian traditions; in the Eastern Orthodox and Western churches; in the Roman Catholic tradition and numerous Reformed divisions. Contemplation on this rich heritage considers the Psalm's contribution to the enrichment and magnification of the liturgy. The richness that the Psalms offer as song book, should be rediscovered and utilised. In this article, selected new Psalms, recently versified in Afrikaans by T T Cloete, are analysed. These Psalms are to be taken into official use on 28 October 2001. The place and function of hymnals is also considered. The church songs are analysed using three criteria: theological, literary, and musicological aspects.